Social cognitive impacts of digital art in metaverse environments: A cross-sectional study of user perception and behavioral patterns - Lin Yang (PLoS ONE, 2026)
This cross-sectional study investigated the social cognitive correlates of digital art in metaverse environments through analysis of user perception and behavioral patterns. The research examined how exposure to digital art within immersive virtual spaces is associated with user cognition and identified demographic factors moderating these associations. Secondary analysis was conducted on multiple datasets including VREED (VR emotion dataset with physiological measures, n = 34), VR eye-tracking data (n = 152), virtual museum navigation records (~7 million), ArtEmis emotion attributions (455K annotations), and WikiArt metadata (80K artworks). Results revealed that digital art exposure showed significant positive associations with aesthetic perception and social value attribution, with moderate effect sizes. Three behavioral exploration patterns emerged: systematic explorers (31.6%), selective browsers (42.1%), and random wanderers (26.3%). Behavioral patterns partially mediated relationships between perception and social cognitive outcomes through emotional resonance, cognitive elaboration, and social mediation pathways. Significant moderation effects were identified for age (U-shaped pattern with strongest associations for 18–25 and 46 + groups), technology proficiency, and cultural background (differential patterns for collectivist versus individualist cultures). The findings demonstrate that digital art experiences in virtual environments are associated with meaningful differences in user perception and social cognition, though associations are moderate and heavily moderated by individual differences. This challenges assumptions about universal effects of metaverse technologies and highlights the need for adaptive, culturally-sensitive approaches to digital art presentation in virtual spaces.